Are ‘Green Brides’ More Attractive? An Empirical Examination of How Prospective Partners’ Environmental Reputation Affects the Trust-Based Mechanism in Alliance Formation - Norheim-Hansen, Anne (Journal of business ethics, 2015)
There is theoretical and empirical evidence that firms’ environmental performance has ramifications for their appeal to various stakeholders. Yet, we know little about how this plays out in the context of strategic alliance formation. Stated differently, research is lacking on how ‘green’ prospective alliance partners are estimated by the initiating firm. This article employs strong environmental reputation as a proxy for high environmental performance and explores implications for the well-established alliance formation trust-based mechanism, under the strategic cognition perspective. The ensuing hypotheses are subjected to empirical scrutiny through an experimental method. A random sample of 138 CEOs and top managers of Norwegian manufacturing firms completed a scenario-based questionnaire. The results show that two out of three trust dimensions are affected and, moreover, that two out of three—but not the same—trust dimensions influence partner attractiveness. Several theoretical and managerial implications, and future research opportunities, are derived from the findings.